Penegakan Hukum Terhadap Pelanggaran atas Larangan Penggunaan Jalan Umum oleh Angkutan Batubara di Kalimantan Selatan - Siti Raihanah; Moh. Hasyim (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
This study aims to analyze the implementation of law enforcement against violations of the prohibition on the use of public roads by coal transporters in South Kalimantan. The research problem formulation includes law enforcement efforts against business axtors violating the prohibition on the use of public roads, the obstacles encountered in enforcing such law, and the compliance of law enforcement with applicable regulations. The research method used is empirical research with primary and secondary data. The approach in this study consists of two types: a legislative approach and a conceptual approach. Data analysis teachniques utilize qualitative analysis, and data collection techniques through literature review and interviews. This study has found several findings. The results indicate that law enforcement against violations of the prohibition on the use of public roads by coal transporters has been implemented, but the application of applicable sanctions has not been optimal